Heterotopic ossification following acute illness: a case report - Litelu, T. I. (University of the Free State, 2018)
Background: Heterotopic ossification is a rare condition typified by formation of bone in extra articular soft tissue. The condition has been linked to several risk factors giving rise to its classification. We report on a case of a 44 year old male patient who was diagnosed with heterotopic ossification following admission for pulmonary TB. The patient does not have the typical risk factors described in recent English language literature. His case is also uncommon due to the diffuse involvement of his joints.
Dissertation (M.Sc. (Internal Medicine)--University of the Free State, 2018
Keywords: Heterotopic ossification; Pulmonary TB; Health risk factors; X-rays; Joints stiffness; Lamellar bone